ANALISIS PERLAKUAN AKUNTANSI ATAS PENDAPATAN DAN BIAYA PADA PT.SKYTECH INDONESIA - Goni, Lesli Mersi; Tinangon, Jantje J.; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2014)
Income is one of the important elements to maximize the profits. Revenue should be measured appropriately so that the revenue will be recognized the right company , so avoid overstate or understate the presentation of the financial statements . According to PSAK No. . 34 ( revised 2010 ) , there are two methods of revenue recognition method used is the percentage of completion and completed contract method . The purpose of this study was to determine the suitability of the recognition of revenue and expenses by PT . Skytech Indonesia with PSAK No. 34 ( revised 2010 ) . The analytical method used is descriptive qualitative , where the data obtained , compiled , categorized , interpreted , and analyzed so as to give a proper picture . The results of the study revealed that the company uses the percentage of completion method on the basis of cost against the cost of which has shown a reasonable value . Similarly, the recognition and measurement of costs associated with the revenue based on the fair value .